Distorted Meanings, Misplaced Justice: A Socio-Legal Approach of the Delegitimization of Domestic Violence Law in Pekalongan, Indonesia - Rismawati, Shinta Dewi; Hardini, Isriani; Mustakim, Zaenal; Adawiyah, Rabiatul; Ladyanna, Sonezza (Nurani, 2025)
Domestic violence remains a persistent social problem in Indonesia despite the enactment of the Law on the Elimination of Domestic Violence (Law No. 23/2004). The persistent discrepancy between legal norms and their enforcement, evidenced by low reporting levels and reliance on non-legal dispute resolution, signals a crisis of legal legitimacy. This study aims to identify public meaning distortions regarding domestic violence in Pekalongan, Central Java Indonesia and analyze their implications for the delegitimization of the law. Employing a socio-legal approach, data were collected through interviews, observations, and questionnaires involving 50 informants in Pekalongan. The findings identify four principal forms of distortion: domestic violence is perceived as a private family matter (38%), a means of discipline or instruction (20%), a source of social disgrace (18%), or an act that is not considered criminal (14%). Only 10% of informants defined it as a legal crime. Consequently, respondents preferred family mediation (34%) or divorce (26%) over court proceedings (10%). Symbolic Interactionism analysis reveals that social interactions prioritize symbols of family harmony and honor over victims' rights, diverting cases from the judicial system. Viewed through the perspective of Symbolic Interactionism, the study finds that social interactions often prioritize family harmony and social honor over the rights of victims, which ultimately diverts cases from the formal justice system. The study concludes that legal ineffectiveness stems from deep semiotic conflicts, underscoring the need to reconstruct public meanings to align domestic violence with criminal justice principles.